Does India's growth matter? Evidence from the SAARC nations - RAY, Rohan (Institutional Knowledge at Singapore Management University, 2019)
The study estimates the extent of spillover effects that India's real per capita gross domestic product (GDP) growth rate has on the growth rates of other countries in the South Asian Association for Regional Cooperation (SAARC) region for the period 2003–2016. It also identifies whether the conventional trade channel is the means through which growth is transmitted from India to her neighboring countries. Using a random effects model, we conclude that on average, a 1 percentage point increase in India's real per capita GDP growth rate results in 0.46 percentage point increase in the per capita GDP growth rates of other SAARC nations. However, this does not occur through the trade channel primarily due to low levels of intraregional trade. Also, using time dummies, the paper analyzes whether there has been any significant change in the degree of spillover effects in the postfinancial crisis period, where countries have been observed to insulate themselves to a certain extent.